Hippo Signaling in Cancer: Lessons From Drosophila Models - Snigdha, Kirti; Gangwani, Karishma Sanjay; Lapalikar, Gauri Vijay; Singh, Amit; Kango-Singh, Madhuri (Frontiers in Cell and Developmental Biology, 2019)
Hippo pathway was initially identified through genetic screens for genes regulating organ size in fruitflies. Recent studies have highlighted the role of Hippo signaling as a key regulator of homeostasis, and in tumorigenesis.. Hippo pathway is comprised of genes that act as tumor suppressor genes like hippo (hpo) and warts (wts), and oncogenes like yorkie (yki). YAP and TAZ are two related mammalian homologs of Drosophila Yki that act as effectors of the Hippo pathway. Hippo signaling deficiency can cause YAP- or TAZ-dependent oncogene addiction for cancer cells. YAP and TAZ are often activated in human malignant cancers. These transcriptional regulators may initiate tumorigenic changes in solid tumors by inducing cancer stem cells and proliferation, culminating in metastasis and chemo-resistance. Given the complex mechanisms (e.g., of the cancer microenvironment, and the extrinsic and intrinsic cues) that overpower YAP/TAZ inhibition, the molecular roles of the Hippo pathway in tumor growth and progression remain poorly defined. Here we review recent findings from studies in whole animal model organism like Drosophila on the role of Hippo signaling regarding its connection to inflammation, tumor microenvironment, and other oncogenic signaling in cancer growth and progression.